Quo vadis development: assessing the livelihood of indigenous people’s communities in Malaysia and the potential for community‑based conservation effort - Zen, Irina Safitri; Saleh, Mohd. Nazeri; Afrizal, Teuku; Yaumidin, Ummi Karomah; Titisari, Prima Wahyu; Hendrayani, Yani (Springer, 2020)
New development activity brings its various impacts for indigenous people often prompting their relocation to a new area. The 1977’s relocation of indigenous people in Royal Belum, Perak State, Malaysia, as part of its rural spatial development, questions on their livelihood in a new resettlement area and their relationship with nature within the current context of development. Despite the provision of basic facilities and infrastructure and the introduction of mono-crop cultivation and agriculture for the indigenous people, they are still practicing the ‘slash and burn’ method and performing their nomadic forest-based lifestyle. This contributes to their living below the poverty line. This present study explains the coexistence of indigenous people in the context of physical development vis-à-vis conservation effort in the Royal Belum. As neglected issue of interactions and conflicts between indigenous peoples and biodiversity conservation, this study outlined the potential of indigenous people’s community-based practices based on the factors: (1) self-belonging of Royal Belum Forest; (2) biodiversity conservation concerns; (3) sustainable development supporter; and (4) wildlife concerns. The indigenous people close relationship with the nature offers a unique stewardship function for co-creation and co-management practices of community-based sustainable ecotourism and agriculture for further enhancement of their livelihood. This effort will support the socio-economic of national physical spatial plan as well as the co-development of conservation of Royal Belum world natural heritage.